A study to correlate trends in perfusion index and bispectral index for assessment of depth of anesthesia: A cross-sectional study - Karthik Raj M; Jain, Shalini; Banjare, Manish; Sharma, Nidhi (Asian Journal of Medical Sciences, 2025)
Background: Accurate anesthesia depth monitoring is crucial for patient safety. Bispectral index (BIS) measures brain activity, whereas perfusion index (PI) reflects peripheral blood flow and sympathetic tone. BIS is a gold standard but is limited by cost and interference, whereas PI is a simpler, more accessible alternative. Aims and Objectives: This study aimed to correlate trends in PI and BIS for assessing anesthesia depth. The primary objective was to examine the correlation between PI and BIS trends. The secondary objective was to monitor intraoperative hemodynamic fluctuations and their relationship with PI and BIS. Materials and Methods: A cross-sectional study was conducted over 12 months at M.G.M. Medical College and M.Y. Hospital, Indore. Seventy patients (18–65 years, the American Society of Anesthesiologists physical status 1 or 2) undergoing elective surgery under general anesthesia were enrolled in the study. Exclusion criteria included cardiovascular, neurological, psychiatric disorders, and peripheral vascular diseases. BIS and PI were monitored throughout the perioperative period. Statistical analysis was done using IBM SPSS Version 22, with significance set at P<0.05. Results: A strong negative correlation between BIS and PI (P<0.05) was found. BIS also showed negative correlations with heart rate, systolic, and diastolic blood pressure (P<0.05). PI had a significant positive correlation with heart rate (P<0.05) and a negative correlation with blood pressure (P<0.05). Conclusion: The significant negative correlation between BIS and PI supports PI as a potential alternative for anesthesia depth monitoring, especially in resource-limited settings.